Development of a workflow for protein sequence analysis based on the Taverna Workbench® Software - Monteiro, Mariana B. (2011)
A workflow based on the Taverna Workbench® software and tentatively named WPSA was developed to perform a generic protein sequence analysis eliminating the need to cut and paste data throughout web applications. The program performs a homology search, a multiple sequence alignment and a phylogeny analysis using PHYLogeny Interface Package (PHYLIP). The workflow designed gives a fast and significant answer to the user about the input sequence entered taking between 5 to 10 minutes to run depending on the Internet connection and web services.